Enantioselective synthesis of quaternary 3, 4-dihydroisoquinolinones via Heck carbonylation reactions: development and application to the synthesis of Minalrestat analogues. Issue 42 (10th September 2019) - Cheng, Cang; Wan, Bin; Zhou, Bo; Gu, Yichao; Zhang, Yanghui
Abstract : A Pd-catalyzed enantioselective intramolecular carbonylative Heck reaction has been developed by using formate esters as the source of CO. Abstract : Minalrestat and its analogues represent structurally novel aldose reductase inhibitors, and the asymmetric synthesis of such pharmaceutically privileged molecules has not been reported yet. We have developed a palladium-catalyzed enantioselective intramolecular carbonylative Heck reaction by using formate esters as the source of CO, which represents the first enantioselective synthesis of quaternary 3, 4-dihydroisoquinolines. The reaction provides a facile and efficient method for the synthesis of enantiopure nitrogen-containing heterocyclic compounds bearing an all-carbon quaternary stereocenter. The reaction has been successfully applied to the first asymmetric synthesis of Minalrestat analogues.